2020
DOI: 10.1088/1741-4326/ab6d40
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the density in Wendelstein 7-X: benefits and limitations

Abstract: In stellarators, increasing the density is beneficial for the energy confinement. While there is no single reason for this observation, it is still very robust across different devices and this is reflected in the empirical energy confinement time scaling for stellarators, ISS04. In order to study whether this is also true for Wendelstein 7-X, the density scaling of the energy confinement time is analyzed and compared to ISS04 for the first divertor experiments. When the density is increased beyond a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 28 publications
3
56
0
Order By: Relevance
“…A broader study of plasma termination, however, is lacking for helical devices and this paper is intended to provide an initial overview of unintended plasma termination in the large helical device (LHD), Wendelstein 7-X (W7-X) and TJ-II. Radiative collapses frequently observed in discharges with highly-radiating edge and scrape-off layer (SOL) regions, however, are not covered in this study but will be reported elsewhere in the context of radiative density limits [1]. While disruptions are not expected in (currentless) stellarator/heliotron operation, thermal quenches are certainly to be illuminated for reactor scale stellarators and heliotrons as well.…”
Section: Introductionmentioning
confidence: 90%
“…A broader study of plasma termination, however, is lacking for helical devices and this paper is intended to provide an initial overview of unintended plasma termination in the large helical device (LHD), Wendelstein 7-X (W7-X) and TJ-II. Radiative collapses frequently observed in discharges with highly-radiating edge and scrape-off layer (SOL) regions, however, are not covered in this study but will be reported elsewhere in the context of radiative density limits [1]. While disruptions are not expected in (currentless) stellarator/heliotron operation, thermal quenches are certainly to be illuminated for reactor scale stellarators and heliotrons as well.…”
Section: Introductionmentioning
confidence: 90%
“…Most critical from perspective of radiation-induced density limits in OP1.2A [6] is the presence of O and C in the plasma edge leading to an effective charge Z eff of up to 3.5 and causing a highly radiative edge mantle. A radiative collapse of the plasma occurred before high core density operation was achieved.…”
Section: Wall Conditions In W7-x Prior To Boronisationsmentioning
confidence: 99%
“…Access to the stellarator-favourable high density operational regime [6] was only possible owing to boronisations in OP1.2B, thus, glow discharges in a 10%B 2 H 6 + 90%He mixture, which deposits a thin B layer on the top surfaces of the first wall and divertor PFCs and getters O. Moreover, the surface coverage also prevents further transient release of water from the graphite plasma-facing sides.…”
Section: Impact Of Boronisation On Impurity Sources In W7-xmentioning
confidence: 99%
See 1 more Smart Citation
“…In W7-X, the impurity radiation usually limits the maximum achievable plasma density [16,43]. In the limiter configuration, the radiation zones are ∼10 cm inside the confined plasma region and almost all of the radiated power comes from the confined plasma region (>90%).…”
Section: Discussion and Summarymentioning
confidence: 99%